Saifuddin, M PENGARUH PENCITRAAN, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP MINAT KULIAH DI POLITEKNIK NSC SURABAYA (Nsc Press, 2014)
Interest as a result of a person's thinking which after looking on the specifications of a productor service, and have a desire to try to meet a need, in this case the consumer will tend to actually choose, weigh and assess whether a product or service that is considered unknown consumers, so that when products or services are actuallyable to meet customer expectations, the consumer incurred an interest to try a product or service. The research method used is quantitative research that researchers did a survey of students, giving questionnaires, data processing, and interpret it. Research carried out by providing some of the questions considered represent three variables that affect the interest of the promotion, imaging, and quality of service. Sampling with a sample of as many as 59 students. Data collection techniques used were questionnaires, interviews, and documentation. Analysis to determine the effect of independent variables and the dependent variable using linear regression analysis. From the analysis it can be seen that the promotion, imaging, and service quality significantly influence student interest.